Dynamic assessment of center of pressure measurements from an instrumented AMTI treadmill with controlled precision. (April 2017) - Fortune, Emma; Crenshaw, Jeremy; Lugade, Vipul; Kaufman, Kenton R.
Highlights: Static COP accuracy comparison of treadmill and ground AMTI force plates. A novel method to assess instrumented treadmill dynamic COP accuracy is proposed. Static treadmill COP error was similar to ground-embedded force plates. Dynamic COP error varied with changes in weight, velocity and shear force. Abstract: With the increasing use of instrumented force treadmills in biomechanical research, it is imperative that the validity of center of pressure (COP) measurements is established. The study aims were to compare an instrumented treadmill's static-belt COP accuracy to that of a floor-embedded platform, develop a novel method to quantify dynamic-belt COP accuracy with controlled precision and perform an initial investigation of how dynamic COP accuracy changes with weight and velocity. Static COP accuracy was assessed by applying a force while moving a rigid rod in a circular clockwise motion at nine positions of interest on the two treadmill and two ground-embedded force plates. Dynamic COP accuracy was assessed for weights (68.0, 102.1, and 136.1 kg), applied through a ball bearing of 2.54 cm circumference, with peak treadmill belt speeds of 0.5, 0.75, and 1.0 m/s. COP accuracy was assessed relative to motion capture marker trajectories. Statically, treadmill COP error was similar to that of the ground-embedded force plates and that reported for other treadmills. Dynamically, COP error appeared to vary systematically with weight and velocity and in the case of anteroposterior COP error, shear force, although testing with a larger number of weights and velocities is needed to fully define the relationship. This novel method can be used to assess any instrumented treadmill's dynamic COP accuracy with controlled precision.